2022
DOI: 10.24925/turjaf.v10i10.1997-2000.5209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Priming on Germination and Seedling Parameters of Cucumber (Cucumis sativus L.) in Lamjung, Nepal.

Abstract: Poor seed germination obstructs the early and uniform seedling emergence at the sub-optimal conditions which can be a major setback to early spring cucumber growers. Different seed priming methods ought to be efficient solutions for the problem. To standardize the best priming method, an experiment was laid out in a Completely randomized design at the Horticulture lab of IAAS, Lamjung Campus. The treatment consisted of demineralized distilled water (hydropriming), hormonal priming (GA3 100ppm and GA3 200 ppm),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The significant effect on the root length of horned melon seedlings, with seeds primed with 2.5 % KNO 3 recording the highest could be attributed to the increase of root length developed by the potassium and nitrate in KNO 3 as it favors the initiation and ramification of the seedling root system. The results from this study tally with the results found by Badu et al [45]. The root length of cucumber seeds (Cucumis sativus L) demonstrated a substantial effect of KNO 3 priming treatments over unprimed seeds.…”
Section: Effect Of Kno 3 On Early Seedling Growth Of Horned Melonsupporting
confidence: 91%
“…The significant effect on the root length of horned melon seedlings, with seeds primed with 2.5 % KNO 3 recording the highest could be attributed to the increase of root length developed by the potassium and nitrate in KNO 3 as it favors the initiation and ramification of the seedling root system. The results from this study tally with the results found by Badu et al [45]. The root length of cucumber seeds (Cucumis sativus L) demonstrated a substantial effect of KNO 3 priming treatments over unprimed seeds.…”
Section: Effect Of Kno 3 On Early Seedling Growth Of Horned Melonsupporting
confidence: 91%
“…Hence, it does not make any agronomic sense to attach much importance to the significant results here. However, other researchers have reported better mean germination times in cucumber, 50 tomato seeds, 51 guava seeds, 52 cowpea seeds. 53 A high germination index shows that germinated seeds appeared faster.…”
Section: Discussionmentioning
confidence: 83%